Water-wet-resistant reusable silicon oxide aerogel material and preparation method thereof
By constructing a silicon oxide aerogel with a gradient porous structure, the problem of easy destruction of traditional silicon oxide aerogels in water absorption or humid environments is solved, and the performance of low thermal conductivity, high temperature resistance and reusable performance is achieved, ensuring heat insulation Performance stability and feasibility of multiple uses.
Patent Information
- Application Number
- CN202411210235.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional silicon oxide aerogel materials are easily damaged in water-absorbing or humid environments, resulting in a degradation of thermal insulation performance and cannot be reusable. The existing hydrophobic treatment methods can only be used for single storage and use.
By constructing a gradient porous structure composed of micropores, mesopores and macropores, using hard template heat treatment and hydrothermal reaction, a silicon oxide aerogel with water-wet resistance and low thermal conductivity is prepared to effectively resist capillary forces and ensure structural stability and Thermal insulation performance.
The low thermal conductivity, high temperature resistance and reusable properties of silica aerogel are achieved, which avoids structural damage and degradation of thermal insulation performance. It can maintain stable performance during multiple soaking and drying processes, and is suitable for long-term intervals. Hot application.
Smart Images

Figure CN119240715A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogel preparation, and in particular to a water-resistant and reusable silicon oxide aerogel material and a preparation method thereof. Background Art
[0002] Aerogel is an amorphous solid material derived from the sol-gel process. Its porosity can reach 80-99.8%, its pore size and colloidal particle size are in the range of 1-10 nanometers and 2-60 nanometers respectively, and its specific surface area can reach 1000m 2 / g or more, density as low as 3kg / m 3 , is a typical nanomaterial. In particular, silica aerogel, which is the most widely studied and has the most mature thermal insulation application, has achieved great development.
[0003] Although silica aerogel has excellent thermal insulation properties, the silica aerogel prepared above is hydrophilic silica aerogel, with silanol groups on the surface, with a coverage of about 5 -OH / nm. 2 . Due to the high specific surface area of aerogel, there are a large number of -OH groups on the surface of silica aerogel, which exhibit strong hydrogen bonding and hydrophilicity and are extremely easy to absorb water. When hydrophilic silica aerogel encounters water or is in humid air, its structure will be destroyed due to moisture absorption, resulting in increased thermal conductivity and decreased thermal insulation performance. In addition, due to the nanosize effect, nano-silica aerogel will sinter at temperatures far below the melting point, causing the skeleton to coarsen and the pore structure to collapse. Traditional silica aerogel materials are treated with hydrophobicity to obtain water-resistant silica aerogels, which have a fatal problem of decomposition of the hydrophobic layer under high temperature conditions. They can only be used for single storage and use, and cannot meet the requirements of reusability.
[0004] Therefore, it is urgent to develop a water-resistant and reusable silica aerogel with an intrinsic hydrophobic structure, rather than a single-use water-resistant aerogel obtained by hydrophobic treatment. Therefore, it is urgent to design a water-resistant, highly efficient heat-insulating and reusable silica aerogel. Summary of the invention
[0005] In order to solve the technical problems existing in the prior art, the present invention provides a reusable silica aerogel with simple preparation process, low thermal conductivity, high temperature resistance, water resistance and its preparation method. The present invention constructs a gradient porous structure composed of micropores, mesopores and macropores to achieve effective resistance to the capillary force generated by the interfacial tension of the liquid during drying. The silica nanoparticles constitute the micropores, which are used to achieve the low thermal conductivity of the aerogel. The mesopores and macropores left after the hard template is removed by heat treatment can greatly weaken the damage of the capillary force to the structure, and the silica aerogel with low thermal conductivity, high temperature resistance, water resistance and reusability is synthesized and prepared.
[0006] In a first aspect, the present invention provides a method for preparing a reusable silica aerogel having low thermal conductivity, high temperature resistance, moisture resistance, and the like, the method comprising the following steps:
[0007] A method for preparing a water-resistant and reusable silicon oxide aerogel material comprises the following steps:
[0008] The silica sol, the macroporous template agent dispersion liquid and the alkaline catalyst are uniformly mixed to obtain a mixed liquid;
[0009] The mixed solution is placed in a sealed container for room temperature curing reaction to obtain a semi-solid gel block, and then further subjected to hydrothermal reaction aging to obtain a solid wet gel block;
[0010] The wet gel block is dried at normal pressure and heat treated to obtain silicon oxide aerogel.
[0011] Furthermore, the macroporous template agent dispersion is a carbon black dispersion or a carbon fiber dispersion.
[0012] Furthermore, the silica sol, the macroporous template dispersion and the alkaline catalyst are uniformly mixed, including:
[0013] The silica sol and the macroporous template are mixed uniformly by mechanical stirring and ultrasonic treatment to obtain a first mixed solution;
[0014] The first mixed solution and the alkaline catalyst are mixed uniformly by mechanical stirring to obtain a second mixed solution.
[0015] Furthermore, the silica sol and the macroporous template agent are mixed uniformly by mechanical stirring and ultrasonic treatment to obtain a first mixed solution, and the specific steps are: adding a carbon black dispersion (or other macroporous template agent dispersion) with a diameter of 50-500nm to a silica sol with a particle size of 10-100nm, the silica sol accounts for 50%-80% of the mass fraction of the obtained mixed solution, and the carbon black (or other macroporous template agent) accounts for 5%-20% of the mass fraction of the mixed solution. After mixing, mechanical stirring is first used for 60 minutes, and then ultrasonic dispersion is performed for 30 minutes.
[0016] Furthermore, the first mixed solution and the alkaline catalyst are mixed uniformly by mechanical stirring to obtain a second mixed solution, and the specific steps are: adding 0.1-10 mol / L ammonia solution of 5% of the total solution mass to the above-mentioned first mixed solution, and continuing to use mechanical stirring for 30 minutes after mixing.
[0017] Furthermore, the above-mentioned mixed solution is placed in a closed container for room temperature curing reaction for 5-48 hours to obtain a semi-solid gel block, and then the hydrothermal reaction is continued at 150-300°C for 5-48 hours for aging to obtain a solid gel block. The specific steps are: pour the mixed solution into a polytetrafluoroethylene container and put it into a reactor, keep it at room temperature for 24 hours, and then continue to keep it in an oven at 150-300°C for 48 hours. After the insulation is completed, a silicon dioxide wet gel with expanded pores of carbon black (or other macroporous template agents) is obtained. The reaction needs to be carried out under fully closed conditions, and the container material needs to ensure that it is a polymer material that does not react with the system.
[0018] Furthermore, the said drying of the wet gel block at normal pressure is to place the obtained wet gel block directly in an oven for drying at normal pressure; the specific steps are: the drying temperature is 50-120° C., and the drying time is 24-48 hours.
[0019] Furthermore, the aerogel is heat-treated to remove the macroporous template agent, and the treatment conditions are: in an air atmosphere, the treatment temperature is 500-800° C., and the treatment time is 0.5-2 h.
[0020] Through the above steps, a water-resistant and reusable silica aerogel material with a gradient pore structure and a preparation method thereof are achieved.
[0021] In a second aspect, the present invention provides a water-resistant and reusable silicon oxide aerogel material prepared by the preparation method described in the first aspect of the present invention.
[0022] Compared with the prior art, the present invention has at least the following beneficial effects:
[0023] (1) Compared with the conventional nanoporous aerogel material with a pore size in the range of 1-10 nm, the present invention has a wider pore size distribution, and the microstructure is composed of macropores driving mesopores and micropore gradient pores. The aerogel has good thermal insulation and temperature resistance, and is also resistant to water and moisture and can be reused.
[0024] (2) The gelation process in the aerogel preparation method of the present invention is a hydrothermal process. Different from the traditional RTM pressure injection process, it is not limited by the shape and size of the reinforcement and can prepare aerogel materials of any shape and thickness.
[0025] (3) The present invention provides a silica aerogel material with a pore size controlled by a macroporous template. The pore size structure of the silica aerogel can be regulated by screening the size of the macroporous template, which is simpler, more accurate and more uniform than the process of adjusting the solid content and pH value of silica sol.
[0026] (4) The basic structure of the aerogel material prepared by the present invention is a gradient pore structure of micropores-mesopores-macropores. Compared with the hydrophobically treated aerogel which can only effectively guarantee the thermal insulation effect for the first use, the structure of this aerogel material does not undergo obvious damage under repeated soaking-drying and repeated high-temperature treatment, and the thermal conductivity does not undergo obvious changes, so it can be reused many times.
[0027] (5) The silica aerogel material prepared by the present invention overcomes the limitations of traditional supercritical drying, such as high energy consumption, high risk, complex and expensive equipment, and can reduce the cost of aerogel preparation and shorten the cycle.
[0028] (6) The present invention can use water as the reaction medium, thus avoiding environmental pollution and waste caused by the use of organic solvents during the preparation process.
[0029] (7) The aerogel material prepared by the method of the present invention has excellent high temperature resistance while maintaining a low thermal conductivity of less than 0.026 W / m·K, and can be used for long-term thermal insulation at 1200°C.
[0030] (8) The pore size of the silica aerogel material prepared by the method of the present invention is 5 to 500 nm, the diameter of the aerogel nanowire is 30 to 200 nm, and the size shrinkage rate after 50 times of soaking in water and drying is ≤2%. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The present invention is a flow chart for preparing the water-resistant and reusable silicon oxide aerogel material.
[0032] Figure 2 This is a SEM image of the water-resistant and reusable silicon oxide aerogel prepared in Example 1 of the present invention.
[0033] Figure 3 This is a comparison of macroscopic photographs of the sample states of the water-resistant and reusable silicon oxide aerogel prepared in Example 1 of the present invention before and after soaking in water and drying.
[0034] Figure 4 This is a curve diagram of the linear shrinkage rate and the soaking-drying times of the water-resistant and reusable silica aerogel prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0036] The present invention provides a method for preparing a water-resistant and reusable silicon oxide aerogel material. The process of the method is as follows: Figure 1 As shown, the following steps are included:
[0037] (1) Silica sol and carbon black dispersion (or other macroporous template dispersion) are mixed to obtain a mixed solution by stirring and ultrasonication.
[0038] The specific steps are as follows: add carbon black dispersion with a diameter of 50-500nm to silica sol with a particle size of 10-100nm, the silica sol accounts for 50%-80% of the mixed solution by mass, and the carbon black accounts for 5%-20% of the mixed solution by mass. After mixing, first use mechanical stirring for 60 minutes, and then ultrasonic dispersion for 30 minutes.
[0039] (2) Mix the above mixed solution and the alkaline catalyst, and continue to mechanically stir them until they are uniform.
[0040] The specific steps are as follows: add 0.1-10 mol / L ammonia solution in an amount of 5% by mass of the total solution to the above mixed solution, and continue to use mechanical stirring for 30 minutes after mixing.
[0041] (3) placing the mixed solution in a sealed container for curing reaction at room temperature for 5-48 hours to obtain a semi-solid gel block, and then continuing to perform hydrothermal reaction at 150-300° C. for 5-48 hours for aging to obtain a solid gel block.
[0042] The specific steps are as follows: pour the mixed solution into a polytetrafluoroethylene container and put it into a reactor, keep it at room temperature for 24 hours, and then keep it in an oven at 150-300°C for 48 hours. After the insulation is completed, a carbon black-pore-enlarged silica wet gel is obtained. The reaction needs to be carried out under fully closed conditions, and the container material needs to be a polymer material that does not react with the system.
[0043] (4) The wet gel block obtained in step (3) is directly placed in an oven for drying at normal pressure.
[0044] The specific steps are: drying temperature is 50-120°C and time is 24-48h.
[0045] (5) The aerogel is heat treated to remove the macroporous template agent, the treatment conditions are: in an air atmosphere, the treatment temperature is 500-800° C., and the treatment time is 0.5-2 h.
[0046] Through the above steps, a water-resistant and reusable silica aerogel material with a gradient pore structure and a preparation method thereof are achieved.
[0047] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments.
[0048] Embodiment 1:
[0049] (1) Silica sol and carbon black dispersion are mixed to obtain a mixed solution by stirring and ultrasonication.
[0050] The specific steps are as follows: add a carbon black dispersion with a diameter of 300 nm to a silica sol with a particle size of 50 nm, wherein the silica sol accounts for 80% by mass in the mixed solution and the carbon black accounts for 15% by mass in the mixed solution. After mixing, mechanical stirring is first used for 60 minutes, and then ultrasonic dispersion is performed for 30 minutes.
[0051] (2) Mix the above mixed solution and the alkaline catalyst, and continue to mechanically stir them until they are uniform.
[0052] The specific steps are as follows: add 3 mol / L ammonia solution, which accounts for 5% of the total solution mass, to the mixed solution, and continue to use mechanical stirring for 30 minutes after mixing.
[0053] (3) The mixed solution is placed in a sealed container for curing reaction at room temperature for 24 hours to obtain a semi-solid gel block, and then further subjected to hydrothermal reaction at 200° C. for 36 hours for aging to obtain a solid gel block.
[0054] The specific steps are as follows: pour the mixed solution into a polytetrafluoroethylene container and put it into a reactor, keep it at room temperature for 24 hours, and then keep it in an oven at 200°C for 36 hours. After the insulation is completed, a carbon black-pore-enlarged silica wet gel is obtained. The reaction needs to be carried out under fully closed conditions, and the container material needs to be a polymer material that does not react with the system.
[0055] (4) The wet gel block obtained in step (3) is directly placed in an oven for drying at normal pressure.
[0056] The specific steps are: carrying out a normal pressure drying process at a temperature of 80°C and a time of 24 hours.
[0057] (5) The aerogel is heat treated to remove the macroporous template agent. The treatment conditions are: in an air atmosphere, the treatment temperature is 500° C., and the treatment time is 0.5 h.
[0058] Through the above steps, a water-resistant and reusable silica aerogel material with a gradient pore structure and a preparation method thereof are achieved.
[0059] The aerogel material prepared in Example 1 has water-resistant performance for repeated use. The mechanical properties and thermal insulation properties of the water-resistant and reusable silica aerogel in Example 1 were tested, and it was found that the surface of the silica aerogel material had no gloss loss, no discoloration, and no shedding. Other performance indicators are shown in Table 1.
[0060] Figure 2 : is a SEM picture of the water-resistant and reusable silica aerogel prepared in this example. Figure 3 This is a comparison of macroscopic photographs of the sample states of the water-resistant and reusable silica aerogel prepared in this example before and after soaking in water and drying. Figure 4 The graph is a graph of the linear shrinkage rate and the soaking-drying times of the water-resistant and reusable silica aerogel prepared in this embodiment.
[0061] Embodiment 2:
[0062] Example 2 is basically the same as Example 1, except that: during the preparation of the mixed solution in step (1), no carbon black dispersion is added.
[0063] The silicon oxide aerogel material prepared in Example 2 does not have water-resistant and reusable properties, and other performance indicators are shown in Table 1.
[0064] Embodiment 3:
[0065] Example 3 is basically the same as Example 1, except that: in the preparation process of the mixed solution in step (1), a carbon fiber dispersion with a diameter of 5 μm and a length of 50-100 μm replaces the carbon black dispersion with a diameter of 50-500 nm.
[0066] The silicon oxide aerogel material prepared in Example 3 has water-resistant and reusable properties, and other performance indicators are shown in Table 1.
[0067] Embodiment 4:
[0068] Example 3 is basically the same as Example 1, except that: during the preparation of the mixed solution in step (1), a carbon black dispersion with a mass fraction of 5% is added to the mixed solution.
[0069] The water-resistance and reusability of the silicon oxide aerogel material in Example 3 are very weak, and other performance indicators are shown in Table 1.
[0070] Embodiment 5:
[0071] Example 5 is basically the same as Example 1, except that during the preparation of the mixed solution in step (1), a carbon black dispersion having a mass fraction of 20% is added to the mixed solution.
[0072] The mechanical strength of the silicon oxide aerogel material in Example 5 is relatively poor, and other performance indicators are shown in Table 1.
[0073] Embodiment 6:
[0074] Example 6 is basically the same as Example 1, except that in the preparation process of the mixed solution in step (1), the mass fraction of silica sol is 50%.
[0075] The strength of the silicon oxide aerogel material in Example 6 is relatively weak, and other performance indicators are shown in Table 1.
[0076] Embodiment 7:
[0077] Example 7 is basically the same as Example 1, except that the temperature in the hydrothermal reaction in step (3) is 150° C. to produce a silicon oxide aerogel material.
[0078] The silicon oxide aerogel material in Example 7 does not have water resistance and reusability, and other performance indicators are shown in Table 1.
[0079] Embodiment 8:
[0080] Example 8 is basically the same as Example 1, except that the hydrothermal reaction time in step (3) is 10 hours to obtain a silicon oxide aerogel material.
[0081] The silicon oxide aerogel material in Example 8 does not have water resistance and reusability, and other performance indicators are shown in Table 1.
[0082] Embodiment 9:
[0083] Example 9 is basically the same as Example 1, except that no heat treatment process is performed to obtain a silicon oxide aerogel material.
[0084] The silicon oxide aerogel material in Example 9 does not have the water-resistant and reusable properties, and other performance indicators are shown in Table 1.
[0085] Embodiment 10:
[0086] Example 10 is basically the same as Example 1, except that the heat treatment process in step (5) is 1000° C. to obtain a silicon oxide aerogel material.
[0087] The silicon oxide aerogel material in Example 10 does not have the water-resistant and reusable properties, and other performance indicators are shown in Table 1.
[0088] Table 1: Performance indicators of a water-resistant and reusable silicon oxide aerogel material prepared in Examples 1 to 10 and an aerogel material of a comparative example.
[0089]
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a water-resistant and reusable silicon oxide aerogel material, characterized in that: The following steps are involved: The silica sol, the macroporous template agent dispersion liquid and the alkaline catalyst are uniformly mixed to obtain a mixed liquid; The mixed solution is placed in a sealed container for room temperature curing reaction to obtain a semi-solid gel block, and then further subjected to hydrothermal reaction aging to obtain a solid wet gel block; The wet gel block is dried at normal pressure and heat treated to obtain silicon oxide aerogel.
2. The method according to claim 1, characterized in that The macroporous template agent dispersion is a carbon black dispersion or a carbon fiber dispersion.
3. The method according to claim 1, characterized in that The silica sol, the macroporous template dispersion and the alkaline catalyst are uniformly mixed, including: The silica sol and the macroporous template are mixed uniformly by mechanical stirring and ultrasonic treatment to obtain a first mixed solution; The first mixed solution and the alkaline catalyst are mixed uniformly by mechanical stirring to obtain a second mixed solution.
4. The method according to claim 3, characterized in that: The silica sol and the macroporous template are mixed uniformly by mechanical stirring and ultrasonic treatment, comprising: A macroporous template agent dispersion with a diameter of 50-500 nm is added to a silica sol with a particle size of 10-100 nm, wherein the mass fraction of the silica sol in the obtained mixed solution is 50%-80%, and the mass fraction of the macroporous template agent in the mixed solution is 5%-20%. After mixing, mechanical stirring was first used for 60 min, and then ultrasonic dispersion was used for 30 min.
5. The method according to claim 3, characterized in that: The step of uniformly mixing the first mixed solution and the alkaline catalyst by mechanical stirring comprises: Add 0.1-10 mol / L ammonia solution in an amount of 5% by mass of the total solution to the first mixed solution, and continue to use mechanical stirring for 30 minutes after mixing.
6. The method according to claim 1, characterized in that The room temperature curing reaction takes 5-48 hours, and the hydrothermal reaction aging reaction is a hydrothermal reaction at 150-300° C. for 5-48 hours.
7. The method according to claim 6, characterized in that The mixed solution is poured into a polytetrafluoroethylene container and placed in a reactor, and is kept at room temperature for 24 hours, and then kept in an oven at 150-300° C. for 48 hours. After the heat preservation is completed, a wet gel block with expanded pores is obtained.
8. The method according to claim 1, characterized in that The drying temperature of the normal pressure drying is 50-120° C. and the time is 24-48 hours.
9. The method according to claim 1, characterized in that: The heat treatment is used to remove the macroporous template agent. The heat treatment conditions are: in an air atmosphere, the treatment temperature is 500-800° C., and the treatment time is 0.5-2 hours.
10. A water-resistant and reusable silicon oxide aerogel material prepared according to the method according to any one of claims 1 to 9.
